Experiences In Implementing a Computerized Vocational Information System In Alberta - Souch, S. G.; Romaniuk, E. (Canadian Journal of Counselling and Psychotherapy, 2012)
A computerized vocational information system has recently been field tested in Alberta. This pilot project, called VISA (Vocational InformationService for Alberta), is the outcome of several months of consultation andcooperation with staff of the Ontario Ministry of Education's StudentGuidance Information Service (SGIS).The experiences of two people primarily responsible for the implementationof VISA in Alberta, on an experimental basis, may be of interest to professional counsellors in other provinces. Representatives of the governments of Ontario and Alberta are optimistic that the exchange of information in career guidance between the two provinces may lead toadded benefits for their respective publics.This paper traces the steps taken in Alberta to implement the SGIS system, describes the procedures, some of the pitfalls, and discusses theVocational Information Service for Alberta in relation to other computer-based systems.